Cephalometric Analysis Difference Between Skeletal and Soft Tissue Measurements - Mehmood, Sundas; Jan, Abdullah; Ijaz, Muska; Ghaffar, Fareena; Bibi, Khadija; Tariq, Alaina (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the skeletal and soft tissue measurements of the dento-facial region in a cephalometric study done in the Pakistani population.Study Design: Comparative cross-sectional study.Place and Duration of Study: Armed Forces Institute of Dentistry, Rawalpindi Pakistan, from Feb to Aug 2019.Methodology: Total 160 subjects were enrolled in the study. Lateral cephalograms were recorded for all the study participants in natural head position. Patients were divided into Class I, II, and III according to the skeletal pattern. The distances of skeletal and soft tissue landmarks relative to the respective norm values and the angles between the Nasion Sella line and Frankfurt horizontal to the natural head position were measured and compared in the three classes using chi-square.Results: Out of 160 patients, 96 (60%) patients were males, and 64 (40%) were females. In our study, 92 (57.5%) patients were classed in class I, 46 (28.75%) in class II and 22 (13.75%) in class III. The mean score of A point, Nasion, and B point angle was 7.5 ± 1.112, while the beta angle was 30.5 ± 2.214. The mean score of facial convexity angle was 14.1 ± 2.124, while the mean vertical height ratio was 1.05 ± 0.11. Both skeletal and soft tissue measurements significantly predict the skeletal pattern and discrepancy (p-value